PENGARUH TINGKAT PENDIDIKAN, STATUS PERKAWINAN PEREMPUAN, DAN JUMLAH ANAK TERHADAP PARTISIPASI PEREMPUAN DALAM PASAR KERJA DI KALIMANTAN BARAT - B01110023, Sylvia Capriaty (Jurnal Curvanomic, 2014)
This study is entitled "Influence of Education Level, Marital Status ofWomen, and the Number of Children Against Women on the Labour Market in WestKalimantan". This study aims to determine the effect of educational level, maritalstatus of women, and the number of children on women's labor participation in WestKalimantan. Female work participation is calculated from the data of Labour ForceParticipation Rate (LFPR).In this study, the writer uses descriptive and quantitative methods were usedto observe the effect between independent variables (education level, marital statusof women and number of children) on the dependent variable (LFPR of women)which is processed to obtain a conclusion. The model used in this study is a multiplelinear regression model which using statistical analysis tools those are F-test,Hypothesis (t-test) and coefficient of determination (R2).From the analysis result, statistic F shows the value 0.000000 withsignificant Î± = 0.05 percent. Significant showed that the education level, maritalstatus of women and number of children simultaneously significant effect on theLFPR of women in West Kalimantan. Meanwhile, based on hypothesis test (t-test),found that low education level (X1), secondary education (X2), higher education(X3), and the number of children (X8) are significantly affect the LFPR of women.While the unmarried status (X4), marital status (X5) divorced status (X6) and divorcedead status (X7) have influence but no significant on LFPR of women. Based ontesting coefficient of determination (R2) obtained Adjusted R-Squared of 0.967726.It means that the education level, marital status of women and number of childrenaffect women's LFPR at 96,77 percent, while 3,23 percent womenâ€™s LFPR isinfluenced by other variables that were not analyzed in the model.Â Keywords : LFPR of women, education level, marital status of women, number ofchildren.